Polymeric nanosystems for near-infrared multispectral photoacoustic imaging: Synthesis, characterization and in vivo evaluation - Liu, Kegang; Wang, Xueya; Ntziachristos, Vasilis; Marsch, Stephan; Hunziker, Patrick (European Polymer Journal, 2017)
Photoacoustic imaging (PAI) is a new biomedical imaging modality based on light-triggered ultrasound emission. For in vivo application, materials with good photoacustic response to illumination in the near-infrared spectrum and suited tissue delivery strategies are needed. We developed polymeric, near-infrared responsive nanomaterials tuned for in vivo application based on oxazoline block copolymer chemistry by living cationic polymerization and a related functional transformation, loaded with a new photonic material, hydrophobized phthalocyanine Zinc complex (H-PcZn), that was efficiently encapsulated into the nanoparticles by self-assembly. The resulting nanoparticles P-NPs and N-NPs bear positive, and negative surface charge, respectively. After physicochemical characterization, applicability of the two nanoparticles as photoacoustic contrast agents was evaluated in vitro and in phantom experiments, where they exhibited excellent PAI contrast. In vivo distribution and visualization of P-NPs and N-NPs following i.v. injection imaged by PAI was confirmed by cryosection fluorescence analysis and showed that the materials accumulated in tissues within 1 h with differential tissue distribution. This pilot study thus describes synthesis of a novel polymeric photoacoustic nanosystem and demonstrates its potential for multimodal, photoacoustic in vivo imaging and for fluorescence imaging.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Amphiphilic copolymer; Biodistribution; Nanoparticle; Photoacoustic agents; Photosensitizer; Theranostic